Alveolar soft part sarcoma: A rare diagnosis - Priyanka Sarkar; Subhabrata Mukherjee; Makhan Lal Saha; Rabi Sankar Biswas (Wolters Kluwer Medknow Publications, 2013)
Alveolar soft-part sarcoma (ASPS) is an extremely rare disease arising from connective tissues with a propensity for recurrence and metastasis. Clinically, it can be confused with hemangioma or arterio-venous malformations. Thus, a high index of suspicion and histopathological examination are required to make a definitive diagnosis. We report a case of recurrent ASPS in a young female with multiple sites involvement without any features of metastasis who has been treated with excision of the symptomatic lesions followed by chemotherapy.